CLUSTER MECHANISM OF NUCLEUS FORMATION AND CONFORMITIES OF PRIMARY CRYSTALLIZATION OF CAST ALLOYS (AT THE EXAMPLE OF HIGH-CHROMIUM CAST IRONS) - N. I. Bestuzhev; A. N. Bestuzhev (Литьë и металлургия)
The theoretical concepts on crystallization of cast alloys on the basis of cluster mechanism of nucleation and growth of initial crystals are given, the technological methods of receiving of fine-grained structure of high-chromium hypercutectic cast irons are outlined.